THE EFFECT OF THE RECIPROCAL TEACHING MODEL ON THE SCIENCE LEARNING OUTCOMES OF GRADE V STUDENTS OF ELEMENTARY SCHOOL INPRES 12/79 POLEWALI, BONE DISTRICT - Sitti Jauhar; Satriani DH; Rezkyamaliyah Ananda (Sains Global Institut, Indonesia, 2026)
This study uses a quantitative approach that aims to determine the effect of the Reciprocal Teaching model on the learning outcomes of fifth-grade students of SD Inpres 12/79 Polewali, Bone Regency. The type of research used is Pre-Experimental Design with One-Group Pretest-Posttest design. The research variables consist of the Reciprocal Teaching model as the independent variable and the learning outcomes of the sciences as the dependent variable, with a total of 24 students as subjects. The data collection technique uses a learning outcome test before and after the application of the Reciprocal Teaching model. Data analysis was carried out through descriptive and inferential statistics. The results showed that the average pretest score was 41.46 and the posttest was 76.88, resulting in an increase of 35.42. The results of the hypothesis test showed a significance value of 0.000 <0.05. Thus, it can be concluded that the Reciprocal Teaching model has a significant effect on the learning outcomes of fifth-grade students of SD Inpres 12/79 Polewali, Bone Regency